2002
DOI: 10.1126/science.1067176
|View full text |Cite
|
Sign up to set email alerts
|

Placebo and Opioid Analgesia-- Imaging a Shared Neuronal Network

Abstract: It has been suggested that placebo analgesia involves both higher order cognitive networks and endogenous opioid systems. The rostral anterior cingulate cortex (rACC) and the brainstem are implicated in opioid analgesia, suggesting a similar role for these structures in placebo analgesia. Using positron emission tomography, we confirmed that both opioid and placebo analgesia are associated with increased activity in the rACC. We also observed a covariation between the activity in the rACC and the brainstem dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

59
878
1
47

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,316 publications
(985 citation statements)
references
References 34 publications
59
878
1
47
Order By: Relevance
“…Using functional magnetic resonance imaging to measure, indirectly, neuronal activity during the administration of placebo with expectation of analgesia, Wager et al [9] showed a significant effect on the activation of the µ-opioid system (dorsolateral prefrontal cortex, rostral anterior cingulate, left nucleus accumbens and right anterior insula). PET studies have shown that in painful conditions placebo will activate the same central structures of the pain matrix as opioids [10].…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using functional magnetic resonance imaging to measure, indirectly, neuronal activity during the administration of placebo with expectation of analgesia, Wager et al [9] showed a significant effect on the activation of the µ-opioid system (dorsolateral prefrontal cortex, rostral anterior cingulate, left nucleus accumbens and right anterior insula). PET studies have shown that in painful conditions placebo will activate the same central structures of the pain matrix as opioids [10].…”
Section: Neurobiological Mechanismsmentioning
confidence: 99%
“…However, the magnitude of these placebo effects in relation to active treatment does not justify the rate of spontaneous resolution, patient expectations (conditioning) and the severity of pain at baseline [12]. Furthermore, the lack of difference between a standard and a novel comparator does not prove the efficacy of the latter in the absence of a placebo group [10][11][12]. In addition, adverse events can only be appreciated when a placebo group is present.…”
Section: The "Nocebo Effect"mentioning
confidence: 99%
“…Additionally, less analgesia-relevant measures have been employed including spectral characteristics of the electroencephalogram (Egan et al, 1996;Hermann et al, 1999;Hoke et al, 1997;Minto et al, 1997a, b), which provides a measure of brain activity, but is not spatially localized, requires doses beyond the normal clinical range and more importantly is not directly associated with pain processing. PET can map the concentration or binding of pharmacological agents over time (Malizia et al, 1996;Pappata et al, 1996) or measure task or drug-induced changes in cerebral blood flow (Petrovic et al, 2002). However, PET is restricted as a tool for examining task-related brain activity by its relatively long measurement time and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Early imaging studies focused on stereotypes (Hart et al, 2000;Phelps et al, 2000), self-knowledge (Kelley et al, 2002), and theory of mind (Baron-Cohen et al, 1994;Frith and Frith, 1999); however, work has now extended into several areas of social psychological inquiry including self-serving biases (Blackwood et al, 2003), self-awareness (Gusnard et al, 2001;Keenan et al, 2001;Eisenberger et al, in press), judgment and decision-making (De Quervain et al, 2004;Sanfey et al, 2003), cooperation (Kosfeld et al, 2005;Rilling et al, 2004), selfschemas , person knowledge (Mitchell et al, 2004a), social exclusion (Eisenberger et al, 2003), attitudinal evaluation (Cunningham et al, 2003;Wood et al, 2005), regulation of stereotypes (Amodio et al, 2003;Richeson et al, 2003;Wheeler and Fiske, 2005), expectancy effects Petrovic et al, 2002;Wager et al, 2004), relational cognition (Aron et al, 2005;Iacoboni et al, 2004), empathy (Carr et al, 2003;Singer et al, 2004), and emotional reappraisal (Beauregard et al, 2001;Ochsner et al, 2002). This special issue devoted to social cognitive neuroscience brings new light to these existing themes (Cunningham, Espinet, DeYoung, and Zelazo, this issue; Mitchell, Banaji, and Macrae, this issue; Ochsner et al, this issue; Sander et al, this issue) and tackles areas new to social cognitive neuroscience such as attribution (Harris, Todorov, and Fiske, this issue; Heberlein and Saxe, this issue), attachment (Gillath, Bunge, Shaver, Wendelken, and Mikulincer, this issue), self-esteem (Pruessner et al, this issue), and intention planning …”
mentioning
confidence: 99%